2015
DOI: 10.5604/12321966.1141384
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of influence of stretching therapy and ergonomic factors on postural control in patients with chronic non-specific low back pain

Abstract: Ergonomic factors are often accompanied by the appearance of LBP. The restrictions within the musculoskeletal system cause disorders in muscle synergies, which is expressed by an increase in the angular velocity of the COG. In patients with chronic back pain syndrome, selected stretching therapy techniques improves the range of motion of the spine and reduces pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 22 publications
1
9
0
1
Order By: Relevance
“…With increasing age, a growth of these disorders could be observed. 17 Gawda et al 18 observed an increase of frontal and sagittal sway as an effect of back pain.…”
Section: Introductionmentioning
confidence: 96%
“…With increasing age, a growth of these disorders could be observed. 17 Gawda et al 18 observed an increase of frontal and sagittal sway as an effect of back pain.…”
Section: Introductionmentioning
confidence: 96%
“…Limitation of negative habits related to irrational management will reduce the deformation of the environment, while at the same time it will secure general obedience to the rules in the working environment. (Brodzińska, 2012;Gawda et al, 2015;Kałuża, 2009;Pawlak & Nowakowicz-Dębek, 2015). Kostecka and Mroczek (2007) show that there is an increased interest in new ways of farming.…”
Section: Resultsmentioning
confidence: 99%
“…While trying to avoid poisoning and exposure to biological, physical and chemical agents, it is necessary to remember about appropriate preventive measures. The use of preventive measures requires thorough knowledge of the scope of their implementation (Brodzińska, 2012;Gawda et al, 2015;Nowakowicz-Dębek et al, 2016;Pawlak & Nowakowicz-Dębek, 2015;Pecyna, Pawlak, Maksym, Filipiuk, & Buczaj, 2016;Walusiak-Skorupy & Pałczyński, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…A more recent study also indicated that the myofascial release therapy is very effective in reducing the pain related disability and improving lumbar range of motion in subjects with mechanical low back pain [32,33]. Besides these interventions, few more studies demonstrated the impact of ergonomic training on low back pain in professionals belonging to different occupational settings [34,35,36].…”
Section: Management Of Postural Low Back Pain Among the Information Tmentioning
confidence: 99%